Interaction of Epstein-Barr Virus Nuclear Antigen Leader Protein (EBNA-LP) with HS1-Associated Protein X-1: Implication of Cytoplasmic Function of EBNA-LP - Kawaguchi, Yasushi (American Society for Microbiology, 2000)
Epstein-Barr virus (EBV) nuclear antigen leader protein (EBNA-LP) consists of W1W2 repeats and a unique C-terminal Y1Y2 domain and has been suggested to play an important role in EBV-induced transformation. To identify the cellular factors interacting with EBNA-LP, we performed a yeast two-hybrid screen, using EBNA-LP cDNA containing four W1W2 repeats as bait and an EBV-transformed human peripheral blood lymphocyte cDNA library as the source of cellular genes. Our results were as follows. (i) All three cDNAs in positive yeast colonies were found to encode the same cellular protein, HS1-associated protein X-1 (HAX-1), which is localized mainly in the cytoplasm and has been suggested to be involved in the regulation of B-cell signal transduction and apoptosis. (ii) Mutational analysis of EBNA-LP revealed that the association with HAX-1 is mediated by the W1W2 repeat domain. (iii) A purified chimeric protein consisting of glutathione S-transferase fused to EBNA-LP specifically formed complexes with HAX-1 transiently expressed in COS-7 cells. (iv) When EBNA-LP and HAX-1 were coexpressed in COS-7 cells, EBNA-LP was specifically coimmunoprecipitated with HAX-1. (v) Careful cell fractionation experiments of an EBV-infected lymphoblastoid cell line revealed that EBNA-LP is localized in the cytoplasm as well as in the nucleus. (vi) When EBNA-LP containing four W1W2 repeats was expressed in COS-7 cells, EBNA-LP was detected mainly in the nucleus by immunofluorescence assay. Interestingly, when EBNA-LP containing a single W1W2 repeat was expressed in COS-7 cells, EBNA-LP was localized predominantly in the cytoplasm and was colocalized with HAX-1. These results indicate that EBNA-LP is in fact present and may have a significant function in the cytoplasm, possibly by interacting with and affecting the function of HAX-1.